From Evaluation to Reflection: The Transformation of Academic Supervision as a Strategy for Teacher Professional Development in Islamic Elementary Schools - Nurul Izzati; Istiqomah Istiqomah; Laela Chusnita; Soedjono Soedjono (FKIP - Universitas Riau, 2026)
Educational quality is strongly influenced by teachers’ competencies and classroom instructional practices. However, academic supervision in many schools remains primarily oriented toward administrative evaluation, limiting its function as a medium for professional reflection. This study aims to analyze the transformation of academic supervision from an evaluative function to a reflective approach as a strategy for teacher professional development at SD Islam Sultan Agung 1 Semarang. This research employed a qualitative approach with a case study design. Data were collected through in-depth interviews, classroom observations, and document analysis involving one principal and four teachers. The data were analyzed using the interactive model of Miles, Huberman, and Saldaña. The findings indicate that academic supervision is implemented systematically through stages of planning, pre-observation, classroom observation, and reflective feedback. Supervision functions not only as a control mechanism but also as a dialogic space that encourages teachers’ critical reflection on instructional strategies, classroom management, and the integration of Islamic values. Supporting factors include collaborative leadership and a positive school culture, while the main challenges are time constraints and variations in teacher competence. These findings highlight that reflective academic supervision contributes significantly to enhancing teacher professionalism and improving the quality of classroom learning.